6.
c) -8(x+2) +3(x+5) = -2(2x+3) 4(2x-1)
17.
a) x-1/3 - x-2/2 = 2x-5/6
b) 2x-1/4 - x-1/2 = 5x-9/4
c) x+6/2 - 5+x/3 = 2-x/6
d) x+4/4 - 2x-1/2 = x+2/4
e) 2x-3/6 - 8-x/9 = x+3/18
f) x+3/3 - 2+x/4 = 3-2x/12

Zamiast tych kreseczek [/] powinna być kreska ułamkowa.

1

Odpowiedzi

2009-04-13T16:55:58+02:00
6.
c)-8(x+2) +3(x+5) = -2(2x+3) 4(2x-1)
-8x - 16 + 3x +15 = - 4x - 6 +(?) 8x - 4
-5x -1 =4x -10
-9x=-9
x=1

17.
a) x-1/3 - x-2/2 = 2x-5/6
2(x-1)/6 -3(x+2)/6 = 2x-5/6
2x - 2 - 3x - 6 / 6 = 2x-5/6
-x -8/6= 2x-6/6 / *6
- x- 8= 2x - 6
-3x=2
x= -2/3

b) 2x-1/4 - x-1/2 = 5x-9/4
2x-1/4 - 2x -2/4= 5x-9/4 /*4
2x-1 - 2x-2=5x-9
-3=5x-9
x=6/5

c) x+6/2 - 5+x/3 = 2-x/6
3x + 18 - 10 + 2x = 2 - x
6x=-6
x=-1

d) x+4/4 - 2x-1/2 = x+2/4
x +2 - 4x -2 = x +2
-4x=2
x= -1/2

e) 2x-3/6 - 8-x/9 = x+3/18
6x - 9 - 16 -2x= x + 3
3x=28
x= 28/3

f) x+3/3 - 2+x/4 = 3-2x/12
4x + 12 - 6 + 3x =3 - 2x
9x=-3
x= -1/3